Analisis Pengaruh Lingkungan Kerja Dan Resistance To Change Terhadap Perilaku Kerja Inovatif Karyawan PT Angkasa Pura I (Persero) Dimediasi Oleh Kepuasan Kerja Dengan Kecerdasan Emosional Sebagai Variabel Moderator - Habibi Karim, Awaludin; Derriawan; Supriyadi, Edy (SEKOLAH PASCASARJANA PRESS, 2021)
President Joko Widodo's policy of opening the door for foreign investors to compete in airport management in Indonesia is a challenge for them PT Angkasa Pura I (Persero). Companies must be able to increase their capacity from all aspects, especially the capacity of creative and innovative Human Resources. This research was conducted with the aim of finding out how much influence the work environment and resistance to change have on employees' innovative work behavior mediated by job satisfaction and the role of emotional intelligence as a moderating variable. Data analysis in this study used a Structure Equation Modeling (SEM) approach to 317 respondents from PT. Angkasa Pura I (Persero). This study concludes that the work environment has no significant effect on the innovative work behavior of PT Angkasa Pura I (Persero) employees. Meanwhile, job satisfaction and resistance to change directly have a significant effect on the innovative work behavior of employees. The work environment can influence the innovative work behavior of employees if it is mediated by job satisfaction. As for resistance to change, if it is mediated by job satisfaction, the negative effect becomes insignificant on innovative work behavior. The results of this study found that the work environment variable had a significant and greatest impact on job satisfaction. Furthermore, the emotional intelligence variable plays a significant role as a moderator in the interaction between resistance to change and employee innovative work behavior.